The innovativeness of rural Europe: A contribution to the concept of innovation - Gilda Farrell; Robert Lukesch (European Regional Science Association (ERSA), 1998)
Rural Europe faces new challenges in an increasingly globalized economy. There are problems of cost competition, outmigration, an ageing population, dispersed settlements, lack of proximity services and employment opportunities. On the other hand opportunities emerge from new demands of the information society, like a healthy environment and typical products of high quality, or space for creative leisure and learning activities, or like a new look to cultural traditions in agriculture and craftsmanship. At the same time the notion of distance has considerably changed due to new telecommunication technologies. The LEADER community initiative is supporting around 800 local action groups (LAG), especially in Objective 1 or 5b rural areas all around Europe; LAG are public-private, public or more rarely private partnerships carrying ou their specific development programme for a smaller region (between 5000 and 100000 inhabitants). The work group on innovation studied and analysed a large number of innovative actions within, but also outside these LEADER areas. The features of the processes revealed that innovation takes place to an astounding extent, and that their specific character even contributes to a better understanding and further development of the concept of innovation. It can be shown that ? Innovation is not a single action, but does have a global character. The whole cycle of action which it comprises over time, sometimes contain quite ?banal" things, carried out step by step, following the logic of trial and error. The innovation lies in the interlinkages and connections which are created between resources, actors, activities and between the local and the external world. ? A cycle of actions is innovative, if it emerges out of a given context and makes this context irreversibly more complex, more dynamic; it creates more alternatives of action and responses than had been disposable before. ? Innovation has a deeply social character. It is fuelled by ?energetic differentials", resulting from different ?speeds" of the local and the global (in terms of productivity, quality requirements, migration flows, nature degradation,...); it really starts, when local actors start to perceive this differential in a new way. During the process new ways of collective learning and of conflict negotiation arise. Finally new common references, values, visions, attitudes or forms of organisation take shape. ? According to the stage of the process, three types of innovation can be distinguished. The first type relates to the mobilisation of people?s energies in the place. It is not directly creating new jobs and wealth, but prepares the soil for their later emergence. They can be characterized as innovations in facilitation and animation. The second type of innovation channels the energies in order to prepare the field for new, coherent and value adding activities. They deal with village renewal, the establishment of quality charts and organisational restructuring of formerly individually squandering actors. The third type of innovation deals with the creation of filieres in the value adding chain of local resources, moreover with the diversifcaton of the local economy and with creating synergies between formerly separate strands of activities. These innovations consolidate new links to the global and consolidate a new position in the economic competition between regions. These and more facts will be delivered by representatives of the work group on the base of selected case studies. Contribution to Theme A: Regional Economics in Transition: Institutional Development and Socio-Economic Change
Keywords: 330